Juridical Review Of Mediation Legal Products Outside Court In Connection With Supreme Court Regulation Number 1 Of 2016 Regarding Mediation Procedure In Court - Arie Supriadi Sanjaya; Denny - Guntara; Muhammad - Abas (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The social dynamics that stand up in recent times maintain to amplify so all of sudden that it has caused the formation of intense opposition schemes in all factors of life that involve stakes and social forces. Conflicts, disputes, and argumentative debates are one of the efforts made through humans to defend their stance and popularity inside the approach of conducting an hobby. Disputes stand up due to the truth there are several interests that conflict with every one of a kind. Basically, dispute resolution can be finished in  methods, what's generally used is dispute resolution via the courts, then with the development of human civilization, dispute resolution outside the court has moreover advanced. The hassle is how the implementation of mediation outdoor the court is connected to Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court and the way binding prison pressure is to the legal products because of mediation outdoor the court docket docket. The technique approach used is normative juridical approach. The result of the studies is article 36 wherein the parties without or with the help of a certified Mediator who efficiently treatment disputes outdoor the Court with a Settlement Agreement can put up a Settlement Agreement to the prepared Court to achieve a Settlement Deed by means of submitting a lawsuit and attached with a Settlement Agreement and files as evidence that suggests the legal relationship of the Parties with the object of the dispute and the peace agreement due to the mediation technique out of doors the court docket docket is best an regular settlement but in fact it's miles all sufficient and is finality.